Germline mutations in the EXT1 and EXT2 genes in Korean patients with hereditary multiple exostoses. - Park, K; Shin, K; Ku, J; Cho, T; Lee, S; Choi, I; Phillipe, C; Monaco, A; Porter, D; Park, J (1999)
Hereditary multiple exostoses (EXT) is an autosomal dominantly inherited disease characterized by the formation of cartilage-capped prominences (exostoses) that develop from the juxtaepiphyseal regions of the long bones. Recently, EXT1 and EXT2 genes were cloned and germline mutations of EXT1 and EXT2 were identified in EXT families. In this study, we performed a mutational analysis of EXT1 and EXT2 genes in eight unrelated Korean EXT families by polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP) analysis followed by direct DNA sequencing. As a result, we were able to identify one family (SNU-OC3) with the EXT1 mutation and another family (SNU-OC15) with the EXT2 mutation. The EXT1 mutation was a 10-bp deletion at the 3' end of exon 5 (CTAATTTAGg) including the splice site of this exon. The EXT2 mutation identified in the SNU-OC15 family was a missense mutation at codon 85 of exon 2 (TGC-->CGC), resulting in an amino acid change from cysteine to arginine. This missense mutation cosegregated with the disease phenotype in this family, suggesting that it is the disease-causing mutation. These two mutations identified in EXT1 and EXT2 are novel ones.